2012
DOI: 10.1002/jor.22182
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of BMP‐2, 4, 7 and AHSG in patients with degenerative joint disease requiring total arthroplasty of the hip and temporomandibular joints

Abstract: To date, there is no objective or reliable means of assessing the severity of degenerative joint disease (DJD) and need for joint replacement surgery. Hence, it is difficult to know when an individual with DJD has reached a point where total arthroplasty is indicated. The purpose of the present study is to determine whether serum levels of Alpha-2 HS-glycoprotein (AHSG) as well as bone morphogenetic proteins (BMP-2, 4, 7) can be used to predict the presence of severe DJD of the hip and/or temporomandibular joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…It is suggested that the unregulation and likely the up regulation of the activity of TGF-β and BMP are likely to make MSCs in numerous joint sites to form excessive amounts of tissues of cartilage, bone and fibre, leading to fibrosis and osteophyte formation, characteristics of joint osteoarthritis. So, any imbalance between the factors above is likely to establish the degenerative joint disease (DJD) which with further progression may lead to the need of a total joint replacement[12]. However, the bone itself has a leading role in the pathogenesis of osteoarthritis.…”
Section: Etiopathology Of Arthritismentioning
confidence: 99%
“…It is suggested that the unregulation and likely the up regulation of the activity of TGF-β and BMP are likely to make MSCs in numerous joint sites to form excessive amounts of tissues of cartilage, bone and fibre, leading to fibrosis and osteophyte formation, characteristics of joint osteoarthritis. So, any imbalance between the factors above is likely to establish the degenerative joint disease (DJD) which with further progression may lead to the need of a total joint replacement[12]. However, the bone itself has a leading role in the pathogenesis of osteoarthritis.…”
Section: Etiopathology Of Arthritismentioning
confidence: 99%
“…Supposed carcinogenicity of rhBMP-2 that was suspected in 2011 [36] is definitively not supported by the largest retrospective study reported by Kelly et al [45] on half a million patients treated for lumbar fusion with and without BMP. As shown by Albilia et al [67], the serum level of BMP is highly correlated with degenerative joint diseases and therefore it is impossible to associate the use of one dose of BMP-2 that disappeared completely of the body after 1 week to be responsible of cancer. This is confirmed by Kelly et al's study [45].…”
Section: Discussionmentioning
confidence: 96%
“…Although BMP-2 was generally thought to play a positive role in cartilage repair, recent data have shown its pleiotropic effects on cartilage hypertrophy and OA (43)(44)(45). BMP-2 has recently been shown to directly bind another cartilage ECM protein, cartilage oligomeric matrix protein (COMP) (46).…”
Section: Discussionmentioning
confidence: 99%